2020
DOI: 10.1080/10408398.2020.1798345
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance associated with the use of antimicrobial processing aids during poultry processing operations: cause for concern?

Abstract: Antimicrobial resistance has become a global issue and a threat to human and animal health. Contamination of poultry carcasses with meat-borne pathogens represents both an economic and a public health concern. The use of antimicrobial processing aids (APA) during poultry processing has contributed to an improvement in the microbiological quality of poultry carcasses. However, the extensive use of these decontaminants has raised concerns about their possible role in the coselection of antibiotic-resistant bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…Several different clones of different MDR Salmonella serovars isolated by placing polystyrene mats beneath a poultry processing line were able to persist on surfaces for several weeks and showed substantial biofilm formation (Dantas et al., 2020), which supports longitudinal studies that have identified resident MDR Salmonella in the poultry slaughterhouse environment (Shang et al., 2019), as well as ineffective cleaning and disinfection of poultry transport crates (Moazzami et al., 2020). Persistent AMR and heavy metal resistant bacteria that have enhanced stress response characteristics and biochemical changes that compromise detection may be selected after exposure to biocides (Mourão et al., 2020; Rhouma et al., 2020). L. monocytogenes strains isolated from the poultry processing environment can also form biofilm, with benzalkonium chloride‐based cleaning programmes showing limited efficacy and exacerbating biofilm formation and AMR expression (Cadena et al., 2019; Rodríguez‐Campos et al., 2019; Puangseree et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Several different clones of different MDR Salmonella serovars isolated by placing polystyrene mats beneath a poultry processing line were able to persist on surfaces for several weeks and showed substantial biofilm formation (Dantas et al., 2020), which supports longitudinal studies that have identified resident MDR Salmonella in the poultry slaughterhouse environment (Shang et al., 2019), as well as ineffective cleaning and disinfection of poultry transport crates (Moazzami et al., 2020). Persistent AMR and heavy metal resistant bacteria that have enhanced stress response characteristics and biochemical changes that compromise detection may be selected after exposure to biocides (Mourão et al., 2020; Rhouma et al., 2020). L. monocytogenes strains isolated from the poultry processing environment can also form biofilm, with benzalkonium chloride‐based cleaning programmes showing limited efficacy and exacerbating biofilm formation and AMR expression (Cadena et al., 2019; Rodríguez‐Campos et al., 2019; Puangseree et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Nutrient‐rich, standard laboratory media such as brain heart infusion (BHI) broth, tryptic soy agar/broth supplemented with yeast extract (TSA/B‐YE) or Mueller Hinton agar (MHA) are often used to study sanitizer efficacy (Kastbjerg & Gram, 2012). However, it is important to consider that nutrient‐rich media contain organic materials, leading to the inactivation of the active compounds in some sanitizers (e.g., chlorine‐based sanitizers; Rhouma et al., 2020; Teng et al., 2018). Additionally, microorganisms can exhibit different stress behaviors when tested in different media (Rantsiou et al., 2012).…”
Section: Antimicrobials and Their Effectivenessmentioning
confidence: 99%
“…A high percentage of unsaturated fatty acids in the bacterial membrane affects cell viability under acidic conditions [ 80 ]. Furthermore, the changes in membrane fluidity and lipid composition can protect bacteria by reducing the permeability of acids and antibiotics [ 86 ].…”
Section: Acid-stress-induced Antibiotic Resistancementioning
confidence: 99%